How will industrial collaborative agglomeration affect the efficiency of regional green development? - Liu, Baoliu; Luo, Jian; Zheng, Kengcheng; Wu, Feng; Zhao, Xiongfei (Frontiers in Ecology and Evolution, 2023)
The integrated development of various industries in China is essential for promoting long-term sustainable development and achieving carbon neutrality. In this study, we analyze panel data from 30 Chinese provinces (excluding Tibet, Hong Kong, Macao, and Taiwan) covering the period between 2005 and 2020 to investigate the impact of collaborative agglomeration between productive service and manufacturing industries on green development efficiency. We utilize a mediation effect model to examine the role of technological innovation in driving the relationship between industrial collaborative agglomeration and regional green development efficiency. Our findings reveal that the collaborative agglomeration of the productive service and manufacturing industries has a significant positive effect on improving regional green development efficiency. We also identify a non-linear relationship, indicating a double threshold effect. Technological innovation plays an important role in facilitating industrial collaborative agglomeration and promoting the efficiency of regional green development. Moreover, our results demonstrate significant regional heterogeneity in the impact of industrial collaborative agglomeration on regional green development efficiency. Based on these findings, we propose several policy recommendations to achieve high-quality regional economic development, including improving the quality of industrial synergy and agglomeration between regions, strengthening the intermediary promotion role of technological innovation, and enhancing regional green productivity.